Exploring the factors that mediate the relationship between accounting ethics and financial reporting quality among MSMEs - Ibrahim Anyass Ahmed; Prince Dacosta Anaman; Mawuena Akosua Cudjoe; Benjamin Akyen; Christian Donkor (Universitas Hayam Wuruk Perbanas, 2024)
This study aims to investigate the impact of accounting ethics on the quality of financial reporting of MSMEs in Ghana, a sector vital to economic stability. Given the critical role of MSMEs in the Ghanaian economy, there is an urgent need to establish ethical financial practices that promote transparency and sustainability in the sector.Using Stakeholder Theory, thisstudy specifically examines how variables of ethical leadership, employee motivation, training and education, regulatory environment, technology solutions, and internal controls affect this relationship.Data were collected from 368 participants in 100 MSMEs from the Central Region of Ghana using a quantitative approach and a standardized questionnaire based on a five-point Likert scale. The main analytical tool for data analysis is Structural Equation Modeling (SEM) with SMART PLS 4. The results of this study indicate that accounting ethics has a significant effect on the quality of financial reporting of MSMEs in Ghana. Ethical leadership, training and education, and employee motivation significantly mediate the relationship between accounting ethics and financial reporting quality of MSMEs in Ghana.Meanwhile, internal control, technology solutions, and regulatory environment do not significantly mediate the relationship between accounting ethics and financial reporting quality of MSMEs in Ghana. This study offers useful insights into the significance of accounting ethics in improving the integrity of financial reporting of MSMEs in Ghana.